Policy Analysis and Characteristics of the Independent Curriculum in Madrasah Aliyah - Dalmi Iskandar Sultani; Dinil Abrar Sulthani (Fitrah: Journal of Islamic Education, 2026)
The implementation of the Independent Curriculum in Madrasah Aliyah presents opportunities to improve the relevance and quality of Islamic education through greater flexibility, contextual learning, and student-centered approaches. However, its implementation still faces challenges related to teacher competence, unequal access to technology, limited learning resources, assessment practices, and institutional readiness. This study aims to examine the characteristics, implementation practices, and main challenges of the Independent Curriculum in Madrasah Aliyah. This study employs a qualitative descriptive approach based on a review of relevant literature on curriculum implementation and Islamic education. The findings indicate that the Independent Curriculum is implemented through curriculum flexibility and local context adaptation, student-centered and differentiated learning, competency development through project-based activities, and formative and authentic assessment. These approaches enable madrasahs to integrate academic competencies with Islamic values, local wisdom, practical skills, and character development. Nevertheless, effective implementation requires continuous teacher professional development, adequate learning resources, technological support, and institutional capacity. The study concludes that the Independent Curriculum has strong potential to strengthen the relevance and quality of Islamic education in Madrasah Aliyah.